On-demand multi-user lightpath sharing through parallel transmission in optical grid networks - WANG Zhen-zhong; LI Hui; JI Yue-feng (Tongxin xuebao)
A lightpath sharing provision method for optical grid networks was proposed. It enables multi grid jobs employ one lightpath simultaneously according to their dynamic requests in their execution time. By aggregating multi grid jobs ef-fectively, data transfer rate of gird applications on the lightpath could approach the maximum bandwidths supported by the lightpath. Experimental results show that, compared to conventional dedicated lightpath based optical grid networks, the proposed scheme could improve network resource utilization remarkably while the QoS of grid application is guaranteed.